Evaluation of effectiveness of Letrozole in treatment of infertility in women with polycystic ovary syndrome (Central Medical College Journal, 2024)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine and metabolic disease,  characterized by hyperandrogenism, oligomenorrhea, and polycystic ovaries. PCOS is one of the most  causes that affect the women of childbearing age, and often leads to infertility. Various managements  were proposed for infertile women with PCOS. However, the optimal management option has not been  addressed satisfied. Although multiple treatments including weight reduction, clomiphene citrate,  metformin, gonadotropins, and ovary cauterization have been reported to treat such condition, the  efficacy still has insufficient evidence to support.Objectives: Purpose of this study was to evaluate the  effectiveness of Letrozole in treatment of infertility in women with polycystic ovary syndrome.Materials  & method: This study was carried out to assess the effectiveness of letrozole and on pregnancy outcomes  including the ovulation induction, pregnancy rate, and endometrial thickness in infertile women with  polycystic ovarian syndrome (PCOS). Total 106 infertile PCOS patients were recruited and allocated in  two groups, Group-L (received letrozole at 2.5 mg twice daily on the 3rd–5th days of menstrual cycle for  5 consecutive days), Group-G 75 U/d−1 gonadotropin through intramuscular injection for 5 days  starting from the third day of menstrual cycle). All patient in both arm completed treatment and  follow-up. Patients in both groups were treated up to 5 treatment cycles. During follow up,  transvaginalultrasonogram (TVS) was performed to see the details of the follicles and the endometrium.  Data was processed and analysed with the help of computer program SPSS and Microsoft excel.  Quantitative data expressed as mean and standard deviation and qualitative data as frequency and  percentage. Comparison was done by tabulation and graphical presentation in the form of tables, pie  chart, graphs, bar diagrams, histogram & charts etc.Result: Mean age of the patient was 26.3 ± 5.7  years in group-L and 25.9 ± 6.1 years in group-G. There were no statistical significant differences  between the 2 groups regarding age, body weight, height, body mass index (BMI). Present study results  showed that patients who received letrozole exert better outcomes in primary endpoint, including  ovulation rate (86.7% in group-L & 62.2% in group-G, P =0.004), endometrial thickness (9.3 ± 1.1 mm  in group-L & 8.5 ± 1.1 mm in group-G, P = 0.003) and pregnancy rate (64.1% in group-L & 30.1% in  group-G, P =0.005). Abortion rate (till the end of 12th week) and multiple pregnancy rate were higher  in group-G, but result were non-significant in between groups. Live birth rate in the letrozole group was  higher 29(54.7%) than group-G 14(26.4%), the difference was statistically significant (P < .05).Conclusion: Patients who took Letrozole had significantly higher endometrial thickness than other  group. Due to the higher pregnancy rate and lower incidence of abortion or multiple pregnancy,  letrozole can be an effective for the treatment of anovulatory subfertility of the PCOS patients.    Central Medical College Journal Vol 7 No 1 January 2023 Page: 13-19